2x+7(x+3)=9(x-1)+5

Simple and best practice solution for 2x+7(x+3)=9(x-1)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+7(x+3)=9(x-1)+5 equation:


Simplifying
2x + 7(x + 3) = 9(x + -1) + 5

Reorder the terms:
2x + 7(3 + x) = 9(x + -1) + 5
2x + (3 * 7 + x * 7) = 9(x + -1) + 5
2x + (21 + 7x) = 9(x + -1) + 5

Reorder the terms:
21 + 2x + 7x = 9(x + -1) + 5

Combine like terms: 2x + 7x = 9x
21 + 9x = 9(x + -1) + 5

Reorder the terms:
21 + 9x = 9(-1 + x) + 5
21 + 9x = (-1 * 9 + x * 9) + 5
21 + 9x = (-9 + 9x) + 5

Reorder the terms:
21 + 9x = -9 + 5 + 9x

Combine like terms: -9 + 5 = -4
21 + 9x = -4 + 9x

Add '-9x' to each side of the equation.
21 + 9x + -9x = -4 + 9x + -9x

Combine like terms: 9x + -9x = 0
21 + 0 = -4 + 9x + -9x
21 = -4 + 9x + -9x

Combine like terms: 9x + -9x = 0
21 = -4 + 0
21 = -4

Solving
21 = -4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8s+15=0 | | 2n^2+13n-24= | | 2z^4-13z^2+36=0 | | 5(n-12)-7n=62 | | 5x-4(x-3)=16 | | 4(4e+1)=12 | | 2x+12-8x=9x-5 | | 5x+15=2x+q | | 3(n-10)-7n=62 | | -9y-39= | | .25+4=18 | | 11m-10m=9m | | 3(n-10)-7n=18 | | 12w-14w=6 | | n-5m=9 | | -2.4x-1=-2.2x+7 | | 5(n-10)-7n=62 | | 9+2=15 | | 17(x-7)=-8-9 | | 3x+4(3x+5)=25 | | 28=2h+18 | | 2x^2-23a+63= | | y+1=-2+7 | | 7(n-12)-52n=62 | | 3px=2q(r-5x)1 | | -2x-1x=-2 | | (2x^2+5-3)=0 | | g-500=225-g | | -(-10+4)+-(-40)= | | 3x^3+x^2-10=0 | | 3t-1=4t+16 | | .5r-.25=.5-.25r |

Equations solver categories